The diagnostic benefit of 16S rDNA PCR examination of infective endocarditis heart valves: a cohort study of 146 surgical cases confirmed by histopathology - Armstrong, Christina; Kuhn, Tim Christian; Dufner, Matthias; Ehlermann, Philipp; Zimmermann, Stefan; Lichtenstern, Christoph; Soethoff, Jasmin; Katus, Hugo; Leuschner, Florian; Heininger, Alexandra (Clinical research in cardiology, 2021)
Upon suspicion of infective endocarditis, the causative microorganism must be identified to optimize treatment. Blood cultures and culturing of removed valves are the mainstay of this diagnosis and should be complemented by growth-independent methods. We assessed the diagnostic benefit of examining removed endocarditis valves by broad-range bacterial PCR to detect causative bacteria in cases where culturing was not available, negative, or inconclusive because a skin commensal was detected, in patients from our clinical routine practice.